B.04 Alterations in brain structure in pediatric migraine. (June 2019) - Rajapakse, T; Mathieu, E; Lindsell, M; Xin, T; Matta, M; Katlariwala, P; Beaulieu, C; Richer, L
Abstract : Background: Migraine is a prevalent and disabling condition with limited understanding in the developing brain. Adults with chronic migraine show structural alterations in pain and sensory processing regions. Similar data is lacking in children and required for early intervention. Methods: Case-control feasibility study assessing structural brain differences between adolescents with chronic migraine and healthy controls using 3T Siemens structural volumetric MRI analysis. Fifteen subjects with chronic migraine were compared to 25 age and sex matched healthy controls. Non-parametric statistics performed (Kruskal-Wallis). Results: Migraine subjects had reduced volumes in total brain (grey and white matter) (KW p <0.03), total thalamus (KW p <0.01) and hippocampal regions (KW p <0.03). Unilateral (right) cerebellar grey matter volumes were significantly reduced in migraine subjects versus controls (KW p<0.05). No significant differences were found in other regions, including basal ganglia, cortical grey matter and brainstem. Conclusions: Total brain, hippocampal and thalamic volumetric reductions are seen in adolescents with chronic migraine. The regions identified are involved in migraine pathogenesis. This volumetric imaging study should improve understanding of the causes and effects of pediatric migraine.